Phytochemical Profiling and Antioxidant Activity of True Leaves and Cotyledons of Adenocaulon himalaicum - Sang-Yun Lee; Nari Yoon; Neil Patrick Uy; Chung-Ho Choi; Sanghyun Lee (ChemEngineering)
Adenocaulon himalaicum is widely distributed across Asia. In its early growth stages, A. himalaicum is traditionally consumed as a food source in Korea. Although previous research has identified the presence of bioactive compounds in A. himalaicum extract, suggesting its potential as a medicinal resource, the phytochemical profile of A. himalaicum extract has not been extensively determined. This investigation aimed to identify the phytochemicals present in the true leaf and cotyledon of A. himalaicum (TLA and CLA, respectively) and evaluate their radical-scavenging activity. By performing LC-MS/MS and HPLC, varying amounts of isochlorogenic acid A, cryptochlorogenic acid, isochlorogenic acid B, rutin, chlorogenic acid, hyperin, and neochlorogenic acid were detected in the TLA and CLA extracts. Chlorogenic acid (9.002 mg/g DW), isochlorogenic acid A (28.512 mg/g DW), and isochlorogenic acid B (12.223 mg/g DW) were the most abundant in TLA. TLA exhibited higher phytochemical content (49.737 mg/g DW), total phenolic content (45.51 mg tannic acid equivalent/g extract), and total flavonoid content (16.24 mg quercetin equivalent/g extract) than CLA. Moreover, the radical-scavenging activity of TLA was two times higher than that of CLA. The young leaf of A. himalaicum has a rich phytochemical profile and robust antioxidant activity; hence, it has potential as natural antioxidant sources for human health and valuable pharmacognosy raw materials for pharmaceutical and functional food applications.